Edukasi Pencegahan Masalah Ginjal Akut Anak Pada Posbindu RW 02 dan Kader PKK RW 015 Tugu Cimanggis Depok - Gunawan, Susilawati; Putri, Dinda (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
The increase in cases of Atipica Prgoressive Acute Kidney (GGAPA) in children reached 269 cases with cases of death reaching 50%.The ministry of Health issues a circular letter to carry out mapping, tracing, cross checkhing activities at health service facilities, sources of purchasing on drugs used by patients before receiving treatment at the hospital and appeal to stop giving syrup drugs. Socialization and enlightenment regarding GGAPA are urgently need so that people do not panic and teh community understand teh situation better and take precautions. GGAPA socialization is carreied out at Posbindu Kutilang RW 02 and education for PKK RW 015 so that community understand better about GGAPA and knows the efforts prevention of GGAPA. keyword: GGAPA, Posbindu, PKK, prevention